2019
DOI: 10.3390/w11051089
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Stormwater Quality in Singapore Catchments in 9 Different Types of Land Use

Abstract: Stormwater quality is well known for its highly stochastic nature and not necessarily well explained by mechanistic urban build up and wash off models. Therefore, local empirical data (based on land use) are an essential compliment to statistical analyses of global data. This paper reports on a large-scale monitoring of the 12 key water quality parameters of suspended solids, nutrients, and heavy metals for stormwater runoff in urban discharges from nine urban land uses with varying sizes in Singapore. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…The influent runoff pollutant concentration in this study is significantly lower compared to other studies reported for urban areas [95,96] (Appendix G). Roof runoff generally has a smooth surface, resulting in a cleaner runoff compared to other runoff sources such as pedestrian footpath and road [97].…”
Section: Comparison To Other Bioretention Systems In the Tropicscontrasting
confidence: 83%
“…The influent runoff pollutant concentration in this study is significantly lower compared to other studies reported for urban areas [95,96] (Appendix G). Roof runoff generally has a smooth surface, resulting in a cleaner runoff compared to other runoff sources such as pedestrian footpath and road [97].…”
Section: Comparison To Other Bioretention Systems In the Tropicscontrasting
confidence: 83%
“…Table1). The results can corroborate the suggestions of other authors claiming that risks posed by nutrients running off with rainwater from road facilities are relatively low(Gan et al 2008;Song et al 2019). The opposite trend was observed for NH 4 + .…”
supporting
confidence: 91%
“…The increase in the content of total suspension follows behind pre-treatment devices-e.g. as a result of intensive phytoplankton development (in warm half-year there were signs of bloom) (Sarkar et al, 2014). During the research period, no signs of erosive damage in the reservoirs were found despite the high inclination of their slopes.…”
Section: Types Of Reservoirs-pre-treatmentmentioning
confidence: 81%